2001
DOI: 10.1108/eum0000000005795
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of foreign direct investment: some empirical evidence

Abstract: This paper reports on an empirical study based on 103 Spanish companies which have conducted foreign direct investment (FDI). Built on the eclectic paradigm, it aims at finding out the main ownership, internalization and location factors which affect such internationalization processes. The results confirm the determinant importance of factors such as the existence of specific assets of an intangible nature. They also show that transaction costs and other questions related to knowledge transfer and accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Cultural affinity is also another consideration. Studies on developing countries (Head and Sorensen, 2005) and Spanish multinationals (Galan and Gonzalez-Benito, 2001) identify a relationship between cultural elements and inflow of FDI. ROI is also identified as one microeconomic factor affecting the inflow of FDI.…”
Section: Othersmentioning
confidence: 99%
“…Cultural affinity is also another consideration. Studies on developing countries (Head and Sorensen, 2005) and Spanish multinationals (Galan and Gonzalez-Benito, 2001) identify a relationship between cultural elements and inflow of FDI. ROI is also identified as one microeconomic factor affecting the inflow of FDI.…”
Section: Othersmentioning
confidence: 99%
“…The most popular location is Hong Kong (China), followed by Singapore, Mexico, and China in that order. The breakdown by region is as follows: Latin and Central America (16 countries), Asia (13), Africa (8) and West Asia (Middle East) (4). There are also more highly ranked economies in South-East Asia and South America than in other regions of the developing world ( Table 3).…”
Section: Data and Empirical Analysismentioning
confidence: 98%
“…7 Knack and Keefer [19] found that the institutional environment for economies activity generally determines the ability of emerging economies to catch up to industrial country standards. 8 Recent work has been carried out by several researchers [8,12,15,16,18,20,21,25] among others. 9 The causality link between income and governance is far from being explained: (1) better governance exerts a powerful effect on per capita income; (2) higher incomes lead to improvements in governance; and (3) there are other factors to be considered.…”
Section: Data and Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…China is not usually the first internationalization destination for these companies, they initially invested in markets with more cultural affinity or geographically closer (Galán and González-Benito, 2001). …”
Section: Spanish Company Profile In Chinamentioning
confidence: 99%